THE TALL TARGET (1951) - Alvarez, Max (Crime Films of Anthony Mann, The, 2013)
A Baltimore-bound passenger train pulls into the Jersey City terminal station on a cold winter’s night. Police Inspector Reilly (Regis Toomey) boards the train to await the arrival of Detective Sergeant John Kennedy (Dick Powell). Meanwhile, the latter, having been tipped off about a murder scheduled to occur in Baltimore the next day, seeks help at headquarters from Police Superintendent Stroud (Tom Powers). Kennedy demands Stroud take immediate action, but the superintendent is too busy socializing with cronies in his dark, smoky office to take the sergeant’s warnings seriously. The men present find the whole theory laughable. Disgusted with their